The Genetics Founder Gregor Mendel and His Scientific Heritage in Medal Art - Barshteyn, Victor; Blume, Yaroslav (Cutting Edge Research in Biology Vol. 1, 2022)
Gregor Johann Mendel remains one of the outstanding biologists of the nineteenth century and a source of inspiration for one of the most challenging sciences of our time: genetics. Mendel’s image and scientific legacy are widely reflected in tangible historical sources : philately, philocarty, numismatics (in particular, medal art). The aim of this article is to explore and introduce into scientific biological circulation artistic medals, related to the life and activities of Gregor Mendel - tangible historical sources studied by medal art, a section of a separate historical discipline of numismatics. The work was accomplished using both general scientific (historical, logical) and special (subject-chronological, retrospective) methods. Literature on numismatics and biology, objects from international numismatic auctions, and websites of world mints have all been researched. The artistic interpretations of the life and scientific legacy of Gregor Mendel in award and commemorative table medals of the former Czechoslovakia, the Czech Republic, the USA, Germany, France, Italy, Austria, Portugal and the European Community were studied and introduced into the scientific biological circulation. The results of the analysis of material historical sources - artistic medals allowed us to cover the pages of Gregor Mendel’s biography and scientific activity in a new way.